Risk factors for adult interpersonal violence in suicide attempters - Moberg, Tomas (BMC Psychiatry, 2014)
BACKGROUND: Suicidal and violent behaviours are interlinked and share common biological underpinnings. In the present study we analysed the association between violent behaviour as a child, childhood trauma, adult psychiatric illness, and substance abuse in relation to interpersonal violence as an adult in suicide attempters with mood disorders. METHODS: A total of 161 suicide attempters were diagnosed with Structured Clinical Interviews and assessed with the Karolinska Interpersonal Violence Scale (KIVS) measuring exposure to violence and expressed violent behaviour in childhood (between 6-14 years of age) and during adult life (15 years or older). Ninety five healthy volunteers were used as a comparison group. A logistic regression analysis was conducted with the two KIVS subscales, expressed violent behaviour as a child and exposure to violence in childhood together with substance abuse, personality disorder diagnoses and age as possible predictors of adult interpersonal violence in suicide attempters. RESULTS: Violent behaviour as a child, age and substance abuse were significant predictors of adult interpersonal violence. ROC analysis for the prediction model for adult violence with the KIVS subscale expressed violence as a child gave an AUC of 0.79. Using two predictors: violent behaviour as a child and substance abuse diagnosis gave an AUC of 0.84. The optimal cut-off for the KIVS subscale expressed violence as a child was higher for male suicide attempters. CONCLUSIONS: Violent behaviour in childhood and substance abuse are important risk factors for adult interpersonal violent behaviour in suicide attempters.